Pembayaran Cashless Pada Proses Check In Dan Check Out di Sofitel Bali Nusa Dua Beach Resort: persepsi kegunaan, persepsi kemudahan, penerimaan pengguna terhadap teknologi - Anak Agung Gede Jati Kusuma Putra Pemayun; I Wayan Sunarsa; I Made Sucipta Adnyanana (Program Studi Manajemen Divisi Kamar, 2023)
Cashless-based payments have increased since 2015 with the biggest increase occurring in 2019 with a total transaction of IDR 5.25 billion. Sofitel Bali Nusa Dua Beach itself is one of the hotels in the ITDC Nusa Dua area in which this hotel certainly accepts cashless payments. This study aims to find out whether cashless payments are good or not during the check-in and check-out process at the Sofitel Bali Nusa Beach Resort front desk area. The method of this research is quantitative research with the Technology Acceptance Model approach, collecting research data using research instruments in the form of questionnaires and interviews which will be used to reinforce the data.Â The results of this study show a very good assessment of the 3 Technology Acceptance Model variables, namely perceived usefulness with 4,40, then perceived ease of use with 4,51 and acceptance of IT with 4,54. The average value of the three variables when added together is 4.48 which shows that cashless payments that occur during the check in and check out process in the Sofitel Bali Nusa Dua Beach Resort front desk area are very good.Â